+0  
 
0
39
3
avatar

Solve for z in the following equation:

 

1-iz = -1 + iz + 3z - 2 (where i^2 = -1). Simplify your answer as much as possible.

 Apr 14, 2022
 #1
avatar+55 
-2

z=\(\boxed{\frac{12}{13}-i\frac{8}{13}}\)

 Apr 14, 2022
 #2
avatar+122390 
+1

1 -iz = -1 + iz + 3z - 2            simplify

 

1 - iz  = -3 + 3z + iz

 

1 + 3  = 3z + iz + iz 

 

4 =   (3 + 2i) z

 

z  =   4 / (3 + 2i)           multiply top / bottom  by  3  - 2i

 

z =  [ 4 (3  - 2i) ] /  [ 9 - 4i^2 ]

 

z = [ 12 - 8i ]  /  [ 9 + 4 ]

 

z =  12/13  - (8/13) i

 

 

cool cool cool

 Apr 14, 2022
 #3
avatar+122 
-3

Yeehaw yal correct bth yall get 1,000 each

😎😎😎

 Apr 14, 2022

3 Online Users